Determining Audit Quality in the Accounting Profession with Audit Ethics as a Moderating Variable - Sigit Hermawan; Duwi Rahayu; Sarwenda Biduri; Ruci Arizanda Rahayu; Nur Amalina Nisfa Salisa (Universitas Pasundan, 2021)
Obtaining information about a company’s financial statements has become increasingly important. Thus, highly skilled and expert public accountants are required who can execute their tasks following ethical standards. This study investigates the effects of audit professional skepticism and auditor expertise and integrity on audit quality in the accounting profession, with auditor ethics as the moderating variable. The study sample consisted of 65 auditors working in 14 public accounting firms in Surabaya, Indonesia. Data were collected through questionnaires and then analyzed using the SmartPLS approach. Results indicated that audit professional skepticism and auditor expertise and integrity positively influence audit quality. On one hand, auditor expertise, which is moderated by auditor ethics, positively influences audit quality. On the other hand, audit professional skepticism and integrity, which are moderated by auditor ethics, do not influence audit quality. The findings suggest that auditors must further improve their compliance with ethical standards to strengthen their integrity, which in turn, enables them to produce good audit quality. Furthermore, auditors must always strive to increase their professional skepticism and expertise.